2019
DOI: 10.26480/ecr.02.2018.22.26
|View full text |Cite
|
Sign up to set email alerts
|

Study on Knowledge, Attitude and Practices Towards the Solid Waste Management in Karan District, Mogadishu Somalia

Abstract: Background: Waste management has been a worldwide issue which most countries are finding the best ways of dealing with. Managing waste improperly poses threat to the health of individuals and the environment. Somalia as a developing country, its communities has been facing with a lot of challenges regarding waste management due to actions towards waste management. Objectives: To examine the knowledge, attitudes and practices of communities on waste management and how their actions have affected their health as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
1
1
1
Order By: Relevance
“…This might be due to those individuals who believed that solid waste management practice could lead a healthier life, prevent death related to poor waste management, prevent the risk of infection, promote the quality of the urban environment were more likely to have a favorable attitude and then more intended to solid waste management practice. This finding is also consistent with previous studies such as the study conducted in Karan District, Mogadishu, Somalia [28], which stated that environmental knowledge and attitudes can influence perception of households their awareness and susceptibility to the community-based project. This is similar to the assumption of TPB that states informing and raising awareness about a certain behavior (environmental issues), as well as proper solid waste management, are critical to the success of the goal of recycling household waste.…”
Section: Plos Onesupporting
confidence: 92%
“…This might be due to those individuals who believed that solid waste management practice could lead a healthier life, prevent death related to poor waste management, prevent the risk of infection, promote the quality of the urban environment were more likely to have a favorable attitude and then more intended to solid waste management practice. This finding is also consistent with previous studies such as the study conducted in Karan District, Mogadishu, Somalia [28], which stated that environmental knowledge and attitudes can influence perception of households their awareness and susceptibility to the community-based project. This is similar to the assumption of TPB that states informing and raising awareness about a certain behavior (environmental issues), as well as proper solid waste management, are critical to the success of the goal of recycling household waste.…”
Section: Plos Onesupporting
confidence: 92%
“…Te fnding also revealed that 50.2% of respondents have good knowledge of solid waste handling practices which is lower than other studies conducted in Ethiopia, 81.8% [25], and Somalia, 58.0% [26], whereas 42.2% of study participants have a favorable attitude towards on-site solid waste handling practices and it is lower than other studies, 62.0% in Somalia [26] and 77.5% in another part of Ethiopia [25]. Te level of good practices in this study was 20.2% and lower than in other studies conducted in Somalia, 35.0% [26]. Te possible diference might be the variation in the educational level of the participants.…”
Section: Discussioncontrasting
confidence: 58%
“…Before the actual conduct, pre-testing was carried out to examine the content validity of the questions asked in the survey (including semi-structured interview). All questions were refined based on the feedback from both experts in the field and laymen and were adapted from studies in past literature [30,[33][34][35][36][37][38][39] to improve their reliability and representativeness to the study. The questionnaire survey was constructed using an online survey administration application, Google Form, and distributed through various online platforms (e.g., Facebook, Instagram, and WhatsApp, popular applications in Malaysia).…”
Section: Data Collection and Samplingmentioning
confidence: 99%